POSTMODERN INTERHUMAN RELATIONS, MANIPULATIVE POWER GAMES AND ETHICAL NORMS IN THE NOVEL "DYSSOMNIAS" BY IGOR STANOJOSKI (Philological Studies, 2023)
This paper presents one possible reading of Igor Stanojoski's novel "Dyssomnias" interpreted through Bauman's fluid interpersonal relations and the ethical norms of the postmodern age. It is a novel in which the narrator's personal family drama is intertwined with the collective drama of the revolutionary protests on Maidan Square in 2013 in Ukraine, as well as with the conditions in Macedonian society, fake democracy, psychological warfare, and fake news,and the influence of the new forms of propaganda on the psychological state of the individual.The starting point for the interpretation of the novel is the critical views of Malcolm Waters on globalization and the global village where the interests of powerful transnational structures can be easily incorporated and realized through various manipulations The paper also uses the recommendations of the psychologist Claude Steiner for recognizing and exposing the manipulations of the two involved parties in the global conflicts and their transmission through the working style of of individual media personalities, which then also affects their private love life.Through a detailed analysis of the two parts of the novel, which have as their motto statements from the collection of short stories "War Doesn’t Have a Female Face" by the Nobel laureate Svetlana Aleksievich, the paper concludes that in the postmodern globalized society, in order to achieve the goals of the globalizers, people are often subject to manipulations that have a negative impact on ethics and interpersonal relations. Subsequently, we are still far from the end of unification, which shall be preceded by long exhausting military conflicts involving all resources of humanity.